2017
DOI: 10.1159/000484506
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine-Induced Migration and Odontoblast Differentiation via ROS-Dependent Autophagy in Dental Pulp Stem Cells

Abstract: Background/Aims: As a vital degradation and recycling system, autophagy plays an essential role in regulating the differentiation of stem cells. We previously showed that iron chelator deferoxamine (DFO) could promote the repair ability of dental pulp stem cells (DPSCs). Here, we investigated the effect of DFO in autophagy and the role of autophagy in regulating the migration and odontoblast differentiation of DPSCs. Methods: Transmission electron microscopy, immunofluorescence staining and western blotting we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
4
19
0
Order By: Relevance
“…The stromal-derived factor-1 alpha (SDF-1α)/CXCR4 axis plays a critical role in regulating the trafficking of MSCs toward the target tissue (Cencioni et al 2012). Previous studies have suggested that hypoxia and hypoxia-mimetic agents, such as CoCl 2 or deferoxamine (DFX), may increase the migration of MSCs by increasing the expression of CXCR4 (Li et al 2017;Wang et al 2017). Our study also found that CoCl 2 treatment enhanced SHED migration.…”
Section: Discussionsupporting
confidence: 62%
“…The stromal-derived factor-1 alpha (SDF-1α)/CXCR4 axis plays a critical role in regulating the trafficking of MSCs toward the target tissue (Cencioni et al 2012). Previous studies have suggested that hypoxia and hypoxia-mimetic agents, such as CoCl 2 or deferoxamine (DFX), may increase the migration of MSCs by increasing the expression of CXCR4 (Li et al 2017;Wang et al 2017). Our study also found that CoCl 2 treatment enhanced SHED migration.…”
Section: Discussionsupporting
confidence: 62%
“…The increased chelatable iron catalyzes excess Fenton reactions, contributing to the production of ROS [34,35,36,37,38]. Moreover, as a hypoxia-mimic compound, DFO increased ROS accumulation in various cells [20,21,39]. In the present study, DFO induced cellular and mitochondrial ROS generation in MCF-7 and MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 52%
“…For instance, chetomin, an inhibitor of the HIF1A/p300 interaction, can inhibit tumor cell growth of MM (69). Due to the function of HIF1A in inducing autophagy, the suppressive effects of inhibitors of HIF1A could exert their effect by modulating the autophagy of MM cells (70)(71)(72)(73). The expression levels of EIF4EBP1, which is a target of mTOR, have been reported to be upregulated for MM cases (74).…”
Section: Discussionmentioning
confidence: 99%